2022
DOI: 10.1021/acs.chemmater.2c01190
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanism of Metal–Organic Framework Drug Nanocarriers Studied by Solid-State Nuclear Magnetic Resonance and X-ray Absorption Near-Edge Structure Spectroscopy

Abstract: Metal-organic framework nanoparticles (nanoMOFs) are novel porous drug delivery systems whose features include high drug loading capacity, versatile functionalization, biocompatibility, and biodegradability. However, little knowledge about the nature of nanoMOFs degradation mechanism is one of many reasons that prevents their clinical use. MIL-100 (MIL stands for Matériaux de l'Institut Lavoisier) is among the most studied nanoMOF for drug delivery.Here, we investigate at the atomic scale the degradation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 63 publications
5
21
0
Order By: Relevance
“…Globally, the profiles of trimesate release from both nanoMIL-100s consist of two stages: (i) a fast stage in the first 3 h after incubation in PBS and (ii) a subsequent gradual stage until the equilibrium is reached after around 24 h. Other authors, including us, also found this time-dependent release pattern. 27,28,40,41 In this investigation, we demonstrate that the phosphate-to-metal molar ratio (P/M) directly influences the extent of nanoMIL-100 degradation. When incubating nanoMIL-100 in deionized (DI) water with no phosphate, a negligible amount of trimesate was detected by lqNMR, less than 2% in the case of nanoMIL-100(Al) and nonobservable for nanoMIL-100 (Fe).…”
Section: Degradation Mechanisms Of Original Nanomil-100(al) and Nanom...mentioning
confidence: 81%
See 2 more Smart Citations
“…Globally, the profiles of trimesate release from both nanoMIL-100s consist of two stages: (i) a fast stage in the first 3 h after incubation in PBS and (ii) a subsequent gradual stage until the equilibrium is reached after around 24 h. Other authors, including us, also found this time-dependent release pattern. 27,28,40,41 In this investigation, we demonstrate that the phosphate-to-metal molar ratio (P/M) directly influences the extent of nanoMIL-100 degradation. When incubating nanoMIL-100 in deionized (DI) water with no phosphate, a negligible amount of trimesate was detected by lqNMR, less than 2% in the case of nanoMIL-100(Al) and nonobservable for nanoMIL-100 (Fe).…”
Section: Degradation Mechanisms Of Original Nanomil-100(al) and Nanom...mentioning
confidence: 81%
“…The triphosphate ATP is a much stronger complexing ligand toward metal(III) cations than AMP; thus, breaking the coordination between ATP and Al(III) is more difficult. As we hypothesized, 41 PBS probably attacks the Al−O−C bond with trimesate first, forming the 6coordinate Al−O−P observed at −2 to −5 ppm in the 27 Al NMR spectrum. Then, ATP is substituted by PBS and released from MIL-100(Al).…”
Section: Degradation and Drugmentioning
confidence: 81%
See 1 more Smart Citation
“…Solid-state NMR is frequently utilized to analyze the chemical composition of various MOF composites. The relative molar ratio between MIL-53 and PDMS in a series of PDMS-coated MIL-53 is directly determined from the 1 H MAS NMR spectra, which is summarized in Table S1. The molecular formula for representing the chemical composition of MIL-53@PDMS-10, MIL-53@PDMS-20, MIL-53@PDMS-30, MIL-53@PDMS-40, and MIL-53@PDMS-60 can be described as [Al­(OH)­(BDC)]­[Si­(CH 3 ) 2 O] 0.3 , [Al­(OH)­(BDC)]­[Si­(CH 3 ) 2 O] 1.0 , [Al­(OH)­(BDC)]­[Si­(CH 3 ) 2 O] 1.5 , [Al­(OH)­(BDC)]­[Si­(CH 3 ) 2 O] 2.7 , and [Al­(OH)­(BDC)]­[Si­(CH 3 ) 2 O] 3.0 , respectively (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…[44] In addition, there has been much work on the MOF degradation (e.g., ZIF-8 and MIL-100(Fe)) in phosphate-containing media. [45,46]…”
Section: Introductionmentioning
confidence: 99%